2010
DOI: 10.1017/s026303461000039x
|View full text |Cite
|
Sign up to set email alerts
|

Charged particle acceleration by electron Bernstein wave in a plasma channel

Abstract: A model of electron acceleration by an electron Bernstein mode in a parabolic density profile is developed. The mode has a Gaussian profile. It could be excited via the mode conversion of an electromagnetic wave or by an electron beam. As it attains a large amplitude, it axially traps electrons moving close to its parallel phase velocity, where parallel refers to the direction of static magnetic field. As the electrons are accelerated and tend to get out of phase with the wave, the transverse field of the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This occurs because Bernstein wave is aligned on the polarization direction of laser beam. Since in our previous results [3,9], we have shown that EBW is supported by large perpendicular component of wave vector and its motion is perpendicular to dc magnetic field. Therefore, large amplitude EBW aided nanocluster plasma might have excited and heating of electron is occurred by high frequency laser beams.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…This occurs because Bernstein wave is aligned on the polarization direction of laser beam. Since in our previous results [3,9], we have shown that EBW is supported by large perpendicular component of wave vector and its motion is perpendicular to dc magnetic field. Therefore, large amplitude EBW aided nanocluster plasma might have excited and heating of electron is occurred by high frequency laser beams.…”
Section: Resultsmentioning
confidence: 53%
“…Over the last few years, beat wave excitation and heating of plasma as well as nanocluster plasma has been a particular field of interest due to its diverse applications in current drive experiments, terahertz radiation generation, acceleration of charge particles and diagnostics [1][2][3][4][5][6][7][8]. Although earlier studies of plasma excitations have been performed by several groups [9][10][11][12], a cluster adds new quantities to so called surface plasmons that enhance the excitation efficiency [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption of high-power lasers in plasmas has been an interesting topic for research over the past several years because it offers very promising applications such as fast and shock ignition scenarios in inertial confinement fusion [1,2], plasma heating [3], high-energy beam production [4], plasmabased particle acceleration [5,6], and phenomenological astrophysics [7]. The nonlinear laser energy absorption process in an underdense plasma is considerably supported by converting the laser energy into high-gradient plasma wakefields damped in the plasma through nonlinear effects [8].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma channeling is one of the most fascinating off-shoots of laser plasma interaction research, due to its potential applications in laser guiding in atmosphere (Alexeev et al, 2005;Woste et al, 2006) particle acceleration (Geddes et al, 2004;Kumar et al, 2010) transportation of ion beams (Penache et al, 2002), in the development of X-ray lasers (Chou et al, 2007;Zhao et al, 2008) etc. To date, however, laser propagation has been severely limited by the lack of a controllable method for extending the propagation distance of the focused laser pulse.…”
Section: Introductionmentioning
confidence: 99%